2007
DOI: 10.1097/meg.0b013e328011438b
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of elevated liver enzymes in blood donors: associations with male gender and central adiposity

Abstract: More than 15% of Greek blood donors exhibit elevated liver enzymes, most likely as a result of unrecognized nonalcoholic fatty liver disease. The prevalence of nonalcoholic fatty liver disease is mainly associated with male sex, obesity and waist circumference, but it may range significantly among different population groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
30

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 18 publications
5
27
1
30
Order By: Relevance
“…However, it is known that men represent the majority of blood donors with reactive serology, with prevalence ranging from 76% to 84% [21][22] . The average age of 37 years-old is similar to that described by other authors, ranging between 34 and 41 years-old [23][24] . Higher mean age in this study was independently associated with seropositivity for viral hepatitis.…”
Section: Conflict Of Interest Referencessupporting
confidence: 87%
“…However, it is known that men represent the majority of blood donors with reactive serology, with prevalence ranging from 76% to 84% [21][22] . The average age of 37 years-old is similar to that described by other authors, ranging between 34 and 41 years-old [23][24] . Higher mean age in this study was independently associated with seropositivity for viral hepatitis.…”
Section: Conflict Of Interest Referencessupporting
confidence: 87%
“…The anti-HBc hepatitis marker was observed frequently, whereas HBsAg was less frequent (10) (16) (17) (18) . The mean age between 34 and 39 years was similar to that described in the literature (19) (20) (21) . The current study found that 31% of the referred individuals were female, and this percentage is consistent with the fi ndings of other studies, which reported a female prevalence from 2.1% to 47% among blood donors (16) (19) (22) (23) (24) .…”
Section: Discussionsupporting
confidence: 83%
“…According to Guerrini et al [35], heavy drinking is overrepresented in the male population. Papatheodoridis et al [36] reported that up to 15% of Greek blood donors show elevated liver enzyme levels that are most likely due to NASH. They also found a strong association of NASH with the male sex, which suggests that earlier diagnosis of HCV infection in men might be due to a higher frequency of elevated liver enzyme levels in the male population.…”
Section: Discussionmentioning
confidence: 99%